1997
DOI: 10.1007/s004380050611
|View full text |Cite
|
Sign up to set email alerts
|

The STT3 protein is a component of the yeast oligosaccharyltransferase complex

Abstract: N-linked protein glycosylation is an essential process in eukaryotic cells. In the central reaction, the oligosaccharyltransferase (OTase) catalyzes the transfer of the oligosaccharide Glc3Man9GlcNac2 from dolicholpyrophosphate onto asparagine residues of nascent polypeptide chains in the lumen of the endoplasmic reticulum. The product of the essential gene STT3 is required for OTase activity in vivo, but is not present in highly purified OTase preparations. Using affinity purification of a tagged Stt3 protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 26 publications
3
72
0
Order By: Relevance
“…Combinations of primers from outside both ends of the disrupted gene (ScProm and ScTerm) yielded the exclusive presence of either 2,936-or 2,355-bp fragments when template DNA was derived from strains carrying intact yeast STT3 ( That the protozoan protein was actually forming part of the complex was shown by using a HA-tagged version of it in a pull-down experiment in which material immunoprecipitated with Ost1p antiserum was run on gels under dissociating conditions. This antiserum was chosen for immunoprecipitation to ensure that the eventual detection of Stt3p in the immunoprecipitate would actually indicate that the catalytic subunit was forming part of the entire complex, because Stt3p and Ost1p belong to different subcomplexes within the three that form the entire yeast OST complex (15,16). Western blot analysis with HA antiserum revealed the presence of Stt3p in the tagged OST complex but not in the wild-type yeast version ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Combinations of primers from outside both ends of the disrupted gene (ScProm and ScTerm) yielded the exclusive presence of either 2,936-or 2,355-bp fragments when template DNA was derived from strains carrying intact yeast STT3 ( That the protozoan protein was actually forming part of the complex was shown by using a HA-tagged version of it in a pull-down experiment in which material immunoprecipitated with Ost1p antiserum was run on gels under dissociating conditions. This antiserum was chosen for immunoprecipitation to ensure that the eventual detection of Stt3p in the immunoprecipitate would actually indicate that the catalytic subunit was forming part of the entire complex, because Stt3p and Ost1p belong to different subcomplexes within the three that form the entire yeast OST complex (15,16). Western blot analysis with HA antiserum revealed the presence of Stt3p in the tagged OST complex but not in the wild-type yeast version ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Yeast STT3 and orthologous proteins in other organisms function as an OST subunit (Karaoglu et al, 1997;Spirig et al, 1997). Neither AtSTT3a nor AtSTT3b cDNA suppressed stt3 mutations in S. cerevisiae (data not shown).…”
Section: Stt3a Functions In Protein N-glycosylationmentioning
confidence: 92%
“…Thus, stt3a-1 and stt3b-1 could encode peptides that have C-terminal truncations after the transmembrane region ( Figure 7C). Several yeast stt3 alleles have been mapped to the C-terminal domain that would not be present in the truncated proteins (Spirig et al, 1997), and based on the yeast paradigm, Arabidopsis stt3a-1 and stt3b-1 are predicted to result in dysfunctional proteins. RT-PCR analysis indicated that STT3a expression occurs in the root and the shoot, whereas STT3b transcript is more abundant in the root than in the shoot ( Figure 8).…”
Section: Stt3a and Stt3b Encode Proteins Homologous With The Endomembmentioning
confidence: 99%
“…In recent years, it has become clear that nine membrane proteins (Ost1p, Wbp1p, Swp1p, Ost2p, Ost3p, Ost4p, Ost5p, Ost6p, and Stt3p) are components of the OT complex in Saccharomyces cerevisiae through the use of genetic tools such as overexpression and synthetic lethality as well as immunological techniques (5)(6)(7)(8)(9)(10)(11)(12)(13). Furthermore, it has been shown that eight of these nine proteins in OT exist in three subcomplexes (I, Ost1p-Ost5p; II, Wbp1p-Swp1p-Ost2p; III, Ost3p-Ost4p-Stt3p) in the endoplasmic reticulum (ER) membrane (2,14,15).…”
mentioning
confidence: 99%